2011
DOI: 10.1111/j.1365-2516.2011.02436.x
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study to describe the incidence of moderate to severe allergic reactions to factor IX in subjects with haemophilia B

Abstract: Using a patient chart review process, we conducted a retrospective study to describe the frequency of allergic reactions in individuals with haemophilia B receiving factor IX (FIX) replacement therapy. The number of allergic reactions in individuals receiving a recombinant FIX (rFIX) product (BeneFix(®)) was then compared with the number of reactions in patients receiving plasma-derived FIX (pdFIX) products. Of the 180 subjects in the study, 163 received rFIX, 88 received pdFIX; 71 received both product types.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 10 publications
2
26
0
2
Order By: Relevance
“…The registry data reported herein for reformulated nonacog alfa supports the safety of nonacog alfa as reported in previous clinical trials in adults and children [8][9][10] and in a retrospective safety analysis [11]. As can be seen in Table 5, adverse events reported in those studies were similar in type and incidence to those reported in this registry.…”
Section: Discussionsupporting
confidence: 90%
“…The registry data reported herein for reformulated nonacog alfa supports the safety of nonacog alfa as reported in previous clinical trials in adults and children [8][9][10] and in a retrospective safety analysis [11]. As can be seen in Table 5, adverse events reported in those studies were similar in type and incidence to those reported in this registry.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, it is well known that allergic or anaphylactoid reactions often occur concurrently with inhibitor development, although the cause of this comanifestation has not yet been elucidated [34,35]. In a recent retrospective analysis of allergic reactions in patients receiving FIX replacement therapy, seven of 180 patients (3.9%) had a moderate or severe allergic reaction to a FIX replacement product, of whom four also developed FIX inhibitors [36]. Results of our pooled analysis are generally consistent with the literature; inhibitors were reported in five (1.2%) patients, four of whom also exhibited allergic-type manifestations.…”
Section: Discussionmentioning
confidence: 99%
“…The same studies showed that no adverse effects such as thrombotic events or viral transmission could be related to rFIX administration. Table 3 summarizes the most important published clinical studies on rFIX products 25–27,32,3841. Only a few studies have specifically compared pdFIX and rFIX concentrates,25,26,35,38,41 confirming the lower recovery rate of recombinant product but documenting their equivalence in terms of efficacy rate.…”
Section: Current Fix Therapiesmentioning
confidence: 97%